ANALISIS MINAT MELANJUTKAN KULIAH PADA SISWA SMA NEGERI 1 SEMPARUK KABUPATEN SAMBAS - Alda, Alda; Witarsa, Witarsa; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to find out how interested students in SMA Negeri 1 Semparuk are in continuing their studies, factors that foster interest, as well as obstacles and solutions in growing interest. This research uses a qualitative approach with a qualitative descriptive research type. Three methods of data gathering were used: documentation, interviews, and observation. Data reduction, data presentation, conclusion-making, and verification are all part of data analysis methodologies. Data validity checking techniques use triangulation and reference materials. Research informants were students, teachers, homeroom teachers and school principals. The results of the research show that interest in continuing college among students at SMA Negeri 1 Semparuk is low. Factors that foster student interest include motivation, ideals and family environment. Obstacles or problems for students come from economic factors and self-will. The solution that can be taken is that schools must provide more information about scholarships and other financial assistance, and must provide more guidance and motivation to students regarding continuing their education to college.